A first step in finite-element simulation of a grasping task. (16th December 2016) - Chamoret, Dominique; Bodo, Michèle; Roth, Sébastien
Abstract: This paper investigates a biomechanical aspect of human hand during grasping, using the finite-element method. A realistic three-dimensional finite–element (FE) model of a human hand is developed, including wrist bones, phalanges, soft tissues and skin, reconstructed from medical computed tomography (CT) scan images. Material laws of the literature have been implemented in the model, in order to be able to simulate a simple activity of grasping. In a human design context, this model allows an interesting biomechanical study, which simulates the grasping task in a biofidelic manner. This model is a first step in the modeling of the human hand that can lead to future studies dealing with the interaction of the hand with its environment for the improvement of safety requirements of future products development.